The Immune Response Against Human Cytomegalovirus Links Cellular to Systemic Senescence - John J. Heath; Michael D. Grant (Cells, 2020)
Aging reflects long-term decline in physiological function and integrity. Changes arise at a variable pace governed by time-dependent and -independent mechanisms that are themselves complex, interdependent and variable. Molecular decay produces inferior cells that eventually dominate over healthy counterparts in tissues they comprise. In a form of biological entropy, progression from molecular through cellular to tissue level degeneration culminates in organ disease or dysfunction, affecting systemic health. To better understand time-independent contributors and their potential modulation, common biophysical bases for key molecular and cellular changes underlying age-related physiological deterioration must be delineated. This review addresses the potential contribution of cytomegalovirus (CMV)-driven T cell proliferation to cellular senescence and immunosenescence. We first describe molecular processes imposing cell cycle arrest, the foundation of cellular senescence, then focus on the unique distribution, phenotype and function of CMV-specific CD8+ T cells in the context of cellular senescence and “inflammaging”. Their features position CMV infection as a pathogenic accelerant of immune cell proliferation underlying immune senescence. In human immunodeficiency virus (HIV) infection, where increased inflammation and exaggerated anti-CMV immune responses accelerate immune senescence, CMV infection has emerged as a major factor in unhealthy aging. Thus, we speculate on mechanistic links between CMV-specific CD8+ T-cell expansion, immune senescence and prevalence of age-related disorders in HIV infection.